Exploring the Role of Social Media in Shaping Student Learning Behaviors - Ulfa, Dian Fadillah; S, Reski; Yusrijal, Yusrijal (Educia Journal, 2025)
This research analyzes behavioral changes in student learning through social media platforms through the lens of student perceptions toward social media education use. This study collected data through interviews and focus group discussions as well as participant observation of 25 students from different educational stages by adopting phenomenological analysis. According to the study social media creates meaningful changes to students' learning behavior patterns through tools which help them work together and find materials and stay focused on educational content. Social media benefits education but at the same time creates difficulties caused by interruptions along with superficial learning and adverse effects on psychological well-being. Research outcomes reveal that students employ social media for academic work however the unorganized features of these platforms lead to struggles in deep learning and increases their tendency to put off tasks. The research adds to academic knowledge by studying social media learning effects on students and promotes balanced academic social media strategies for education. Model programs must be developed to use social media tools effectively as educational instruments with proper mechanisms to reduce their adverse impacts and create better organizational systems for digital learning resources. The study generates essential findings which educators together with policymakers need to use for maximizing the benefits of social media learning opportunities.